1981
DOI: 10.1007/bf00251284
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hyperinsulinaemia and arterial glycosaminoglycans in dogs

Abstract: Summary. The effect of insulin on the glycosaminoglycan content of the arterial ground substance was compared in age-matched alloxan-diabetic dogs, hypophysectomized dogs and normal controls. Hyaluronic acid and the three sulphated components, heparan, dermatan and isomeric chondroitin sulphates were quantitatively determined in the arch, thoracic and abdominal aorta, and in the carotid, coronary, iliac, renal and mesenteric arteries. Diabetic animals were either well or poorly controlled. Six well controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Morphological studies of diabetic arteries have shown decreased Alcian blue staining suggesting either a decreased GAG content or altered sulphation of the macromolecules [3]. Data from some studies of experimental diabetes have pointed to an increased hyaluronic acid content in rodent aorta [11,12], others have given less clear results [13], however, there is no information available about the distribution of GAG in tunica media of the human aorta in diabetes. GAG/proteoglycans are considered to be involved in some of the key events which lead to the formation of atherosclerotic lesions [14], e. g. binding of lipoproteins [15,16], platelet aggregation [17], and growth inhibition of smooth muscle cells [18].…”
mentioning
confidence: 93%
“…Morphological studies of diabetic arteries have shown decreased Alcian blue staining suggesting either a decreased GAG content or altered sulphation of the macromolecules [3]. Data from some studies of experimental diabetes have pointed to an increased hyaluronic acid content in rodent aorta [11,12], others have given less clear results [13], however, there is no information available about the distribution of GAG in tunica media of the human aorta in diabetes. GAG/proteoglycans are considered to be involved in some of the key events which lead to the formation of atherosclerotic lesions [14], e. g. binding of lipoproteins [15,16], platelet aggregation [17], and growth inhibition of smooth muscle cells [18].…”
mentioning
confidence: 93%
“…On the basis principally of biochemical evidence, both normal and especially pathologically altered arterial walls appear to be relatively rich in hyaluronan (25,36,53). A number of attempts have also been made to identlfy this non-sulfated glycosaminoglycan histochemically within vascular tissues.…”
Section: Introductionmentioning
confidence: 99%